1978
DOI: 10.1111/j.1699-0463.1978.tb02012.x
|View full text |Cite
|
Sign up to set email alerts
|

Morphometric and Dynamic Studies of Bone Changes in Hypothyroidism

Abstract: Mosekilde, L. & Melsen, F. Morphometric and dynamic studies of bone changes in hypothyroidim. Aota path. microbhl. scand. Sect. A, 86: 56-62, 1978. Born biopsies were performed after tetracycline double-labelling by transfixing the right iliac crest in fourteen hypothymid patients. The bone changes in cortical and trabecular bone were determined by s:mple measurement and point counting on decalcified and undecalcified stained sections and compared to normal controls and to sex and age matched hyperthyroid p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
21
4
2

Year Published

1985
1985
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(30 citation statements)
references
References 8 publications
2
21
4
2
Order By: Relevance
“…Osteoclast activity and bone resorption surfaces were reduced, and osteoblast activity and osteoid apposition were impaired. The bone formation phase in each remodeling cycle was prolonged 4-fold, resulting in an extended period of secondary mineralization (25)(26)(27). In the current studies, D2KO mice similarly had low bone turnover and impaired osteoblast activity with reduced mineralized surfaces and BFR.…”
Section: Discussionmentioning
confidence: 50%
See 2 more Smart Citations
“…Osteoclast activity and bone resorption surfaces were reduced, and osteoblast activity and osteoid apposition were impaired. The bone formation phase in each remodeling cycle was prolonged 4-fold, resulting in an extended period of secondary mineralization (25)(26)(27). In the current studies, D2KO mice similarly had low bone turnover and impaired osteoblast activity with reduced mineralized surfaces and BFR.…”
Section: Discussionmentioning
confidence: 50%
“…Studies of the skeletal consequences of hypothyroidism in humans demonstrated low bone turnover and a prolonged bone remodeling cycle with impaired osteoclast and osteoblast function (25)(26)(27). Osteoclast activity and bone resorption surfaces were reduced, and osteoblast activity and osteoid apposition were impaired.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Veriϐicou-se que agentes reabsortivos, tais como o PTH, 1,25 (OH) 2 D 3 , TNF-α e as interleucinas, induzem a expressão de RANKL. O T3 induz a expressão de RANKL in vitro, mas esse efeito somente é ampliϐicado quando se adiciona 1,25(OH) 2 D em meio de cultivo com osteoblastos, o que sugere a interação dos hormônios tireoidianos com a vitamina D no mecanismo de reabsorção óssea (Mosekilde et al 1978). A deϐiciência dos hormônios tireoidianos reduz o metabolismo geral e afeta diretamente o recrutamento, a diferenciação, a maturação e o metabolismo das células responsáveis pela aposição, mineralização e reabsorção ós-seas (Burkhart & Jowsey 1967, Jowsey & Detenbeck 1969, Mosekilde et al 1978, Eriksen et al 1986, Banavoc & Koren 2000.…”
Section: Interação Da Vitamina D Com Os Hormônios Tireoidianosunclassified
“…O T3 induz a expressão de RANKL in vitro, mas esse efeito somente é ampliϐicado quando se adiciona 1,25(OH) 2 D em meio de cultivo com osteoblastos, o que sugere a interação dos hormônios tireoidianos com a vitamina D no mecanismo de reabsorção óssea (Mosekilde et al 1978). A deϐiciência dos hormônios tireoidianos reduz o metabolismo geral e afeta diretamente o recrutamento, a diferenciação, a maturação e o metabolismo das células responsáveis pela aposição, mineralização e reabsorção ós-seas (Burkhart & Jowsey 1967, Jowsey & Detenbeck 1969, Mosekilde et al 1978, Eriksen et al 1986, Banavoc & Koren 2000. A redução da aposição óssea, no hipotireoidismo, se dá por interferência direta (Burkhart & Jowsey 1967), já que T3 e T4 estimulam a expressão de genes nos osteoblastos para a produção de colágeno e osteocalcina (Ross 1996, Varga et al 1997.…”
Section: Interação Da Vitamina D Com Os Hormônios Tireoidianosunclassified